2016
DOI: 10.1542/peds.2016-0378
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Pregnancy Testing Before Intravenous Cyclophosphamide: A Quality Improvement Study

Abstract: Our institution achieved a significant increase in standard pregnancy screening in adolescent girls receiving intravenous cyclophosphamide. The interventions most valuable in increasing screening rates were updating electronic order sets, educating staff, and physician engagement in the Maintenance of Certification program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…interventions, was previously used to successfully improve adolescent pregnancy screening rates. 21 Despite local contextual factors, we did not observe the magnitude of absolute reduction in unnecessary GAS pharyngitis testing for which we aimed. Cognitive bias likely played a role in unnecessary GAS pharyngitis testing.…”
Section: Figurementioning
confidence: 66%
“…interventions, was previously used to successfully improve adolescent pregnancy screening rates. 21 Despite local contextual factors, we did not observe the magnitude of absolute reduction in unnecessary GAS pharyngitis testing for which we aimed. Cognitive bias likely played a role in unnecessary GAS pharyngitis testing.…”
Section: Figurementioning
confidence: 66%
“…Electronic health records (EHRs) can prompt providers to order pregnancy testing when prescribing cancer treatment. Hayward et al 23 found that including a pregnancy test as part of chemotherapy medication order sets in the EHR was the most effective intervention in increasing pregnancy screening rates among adolescent female patients with cancer. Use of an EHR in this manner is effective and upholds the Centers for Medicare & Medicaid Services EHR Incentive Programs' meaningful use specifications.…”
Section: System Structurementioning
confidence: 99%
“…Characteristics of the included studies are shown in Table 2 and summarized in Appendix B. (Chave et al, 2001;Mulryan et al, 2018) to 95.1% (Cheetham et al, 2006), pregnancy testing during treatment from 12.7% (Raguideau et al, 2015) to 100% (Hayward et al, 2016), contraception use before starting treatment from 15.7% (Uuskula et al, 2018) to 94% (Brandenburg et al, 2017), and contraception use during treatment from 1.7% (Tsur et al, 2008) to 100% (Ozyurt & Kaptanoglu, 2015).…”
Section: Risk Managementmentioning
confidence: 99%